Exploration Process and Genesis Mechanism of Deep Geothermal Resources in the North Jiangsu Basin, East China: From Nothing to Something - Wang, Yibo; Bai, Yang; Wang, Lijuan; Guan, Junpeng; Wang, Yaqi; Wang, Zhuting; Hu, Jie; Hu, Shengbiao (Frontiers in Earth Science, 2021)
Geothermal resources, as an important member of clean renewable energy, of which the exploration, development, and utilization of geothermal resources, especially deep geothermal resources, are of great significance for achieving carbon peaking and carbon neutrality. Taking the North Jiangsu Basin (NJB) as an example, this paper reviews the exploration process of deep geothermal resources in the basin and presents the latest results. The study shows that the NJB is a typical “hot basin” with an average heat flow value of 68 mW/m2. In this region, the deep geothermal resource favorable areas in the NJB are mainly distributed in the depressions, in particular those near the Jianhu uplift, i.e., the Yanfu depression and the Dongtai depression. In addition, the genesis mechanism of the deep geothermal resource favorable area in the NJB is best explained by the “two stages, two sources” thermal concentration, that is, “two stages” means that the transformation of the lithospheric thermal regime are caused by the late Mesozoic craton destruction in East China, and the Cenozoic lithospheric extension; these two tectono-thermal events together lead to the deep anomalous mantle-source heat (the first source), and the upper crustal-scale heat control is mainly caused by thermal refraction (the second source). Overall, this case study underlines new ideas of understanding the geothermal genesis mechanism in East China, which can guide for the exploration and development of deep geothermal resources at the basin scale.